2002
DOI: 10.1590/1983-21172002040203
|View full text |Cite
|
Sign up to set email alerts
|

O Uso Espontâneo De Analogias Por Professores De Biologia: Observações Da Prática Pedagógica

Abstract: ResumoEste artigo é fruto de uma dissertação de mestrado onde evidenciamos o uso de analogias e metáforas de forma espontânea por professores de Biologia no Ensino Médio. Contrariamente à nossa expectativa inicial, baseada na forte presença das coleções didáticas na prática pedagógica dos professores em geral, em nossas observações evidenciamos que poucas das analogias utilizadas coincidem com aquelas presentes nas coleções didáticas adotadas pelas professoras sujeitos da pesquisa. Detectamos outras fontes de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
0
0
8
Order By: Relevance
“…The group indicated that they did not use analogies between a tree and evolution as a formal methodology, despite their view that analogies are important for understanding content. This absence of a formal methodological use supports the research by Pádua (2002), Ferraz and Terrazzan (2002), Monteiro (2005), and Marcelos (2006) regarding the use of A&M in the classroom.…”
Section: Focus Groupsupporting
confidence: 75%
See 1 more Smart Citation
“…The group indicated that they did not use analogies between a tree and evolution as a formal methodology, despite their view that analogies are important for understanding content. This absence of a formal methodological use supports the research by Pádua (2002), Ferraz and Terrazzan (2002), Monteiro (2005), and Marcelos (2006) regarding the use of A&M in the classroom.…”
Section: Focus Groupsupporting
confidence: 75%
“…That is, teachers did not use it in teaching, despite the use of analogies between a tree and evolution to explain content. They also did not employ appropriate methodologies for teaching with analogies, confirming studies by Pádua (2002), Marcelos (2006), Ferraz and Terrazzan (2002), and Monteiro (2005), among others. Based on the data collected, this appears due to lack of knowledge of those methods.…”
Section: Final Considerationssupporting
confidence: 66%
“…Como exemplos de pesquisas em ensino de ciências no Brasil com abordagens sobre analogias destacam-se trabalhos com foco na biologia TERRAZZAN, 2001), química (JUSTI; MENDONÇA, 2008) e física (SILVA; TERRAZZAN, 2011). A presença de analogias foi detectada em livros didáticos brasileiros (TERRAZZAN et al, 2005;FRANCISCO JUNIOR, 2009;ARAUJO;GUIMARÃES, 2017), nos discursos dos professores TERRAZZAN, 2001TERRAZZAN, , 2002TERRAZZAN, , 2003 e de alunos (SILVA; TERRAZZAN, 2009; ZAMBON; TERRAZZAN, 2013) e em revista de divulgação científica brasileira .…”
Section: Introductionunclassified
“…As linhas de investigação sobre o ensino com analogias são promissoras. Dentre elas, há pesquisas que visam identificar e mapear quais são as concepções que professores em exercício (FA-RIAS, BANDEIRA, 2009;FERRAZ, TERRAZZAN, 2002; MOZZER, JUSTI, 2013) e em formação inicial (BOZELLI, NARDI, 2012;FABIÃO, DUARTE, 2005;OLIVEIRA, MOZZER, 2017;RIGOLON, OBARA, 2011) possuem sobre o tema. Essas pesquisas indicam que os pesquisadores compreendem que as concepções de professores, tanto em formação inicial quanto em formação continuada, influenciam o modo como o docente usa a linguagem analógica em sala de aula.…”
Section: Introdução E Fundamentação Teóricaunclassified